Megalithism and Tribal Ritualism: A Passage through the Kurumbas of Attappadi - Manjula Poyil (Advances in Historical Studies, 2013)
The study of mortuary practices of Megalithic communities and its use as the basis for reconstructing the past society is unique in archaeology as it represents the direct and purposeful culmination of conscious behavior of the followers of this cultural trait. There are voluminous studies on the Megalithic builders of South India, including Kerala, written by prominent archaeologists and anthropologists from the early decades of the nineteenth century. Most of them ignored the continuity of Megalithic tradition, except a scant reference to the erection of funeral edifices among tribes like the Kurumbas and Mudugas of Attap- padi and Mala-arayans of the Thiruvananthapuram district of Kerala. A study of the living Megalithic practices provides clues to ethnographic parallels, existing belief systems and habitation sites of the pre- sent communities. The present study discusses the cultural aspects of the rituals related to living Mega- lithic tradition among the Attappadi tribes, of the Palakkad district of Kerala. The study of the mortuary practices of the Kurumbas raises two important questions-firstly, how far this tribe can be seen as the ac- tual successor of Megalithic builders of Kerala and, secondly, how does the social differentiation within the Kurumba community got reflected in its mortuary practices, just like the Megalithic builders of the past.